Determination of apparent kinetic and stoichiometric parameters in a nitrifying fixed-bed reactor by in situ pulse respirometry - Ordaz, Alberto (2011)
The determination of stoichiometric and kinetic parameters of biological processes occurring in fixed-bed reactors is usually achieved through mass balance methods or by the characterization of samples taken from the core of the reactor. Mass balance is time demanding and to obtain representative samples from the core of filter media is often difficult. A fast and non-invasive alternative method might be beneficial. In this paper we explored the potential for using in situ pulse respirometry in a submerged fixed-bed reactor for assessing biological processes. A nitrifying fixed-bed reactor was operated over 85 days while analyzing the dissolved oxygen response to pulses of ammonium. In situ pulse respirometry allowed us to determine the apparent maximum oxygen uptake rate and substrate affinity constant. Additionally, the apparent biomass growth yield was determined during the first 60 days. Unfortunately, after day 60, erratic biomass growth yield results were obtained, which we were unable to explain through hydrodynamic characterization of the reactor. However, it is concluded that in situ pulse respirometry is a potentially useful tool to characterize fixed-bed reactors as an alternative to other methods, such as mass balance.